Gereja, Politik Nilai, dan Tantangan Disintegrasi: Kajian Etika Politik Kristen di Indonesia Kontemporer - Chris Sorongan; Yosep Heristyo E. B.; Immanuel Widjaja M. H.; Maria Wesley; Deo D. A. Pangestu (Sukacita : Jurnal Pendidikan Iman Kristen, 2026)
This revised manuscript expands a reflective essay on the relationship between the Church, value politics, and the threat of national disintegration in contemporary Indonesia. The study addresses previous concerns regarding an underdeveloped methodology, repetitive rhetoric, and limited academic support by framing the article as a qualitative literature-based study with contextual theological analysis. This article argues that the Church is not called to function as an instrument of political legitimation but rather as a public conscience that maintains critical distance from all political powers. By examining the history of church-state relations, the dynamics of identity politics in Indonesia, and key works in Christian political ethics, the study proposes three practical orientations: deconstructing a defensive minority mentality, strengthening value politics based on justice and the common good, and transforming the Church into an inclusive public space that promotes interfaith dialogue and civic solidarity. The conceptual conclusion highlights that the Church’s response to polarization should not be characterized by apathy or pragmatic alignment with political elites, but through a disciplined, prophetic, and constructive witness in public life.